2011
DOI: 10.3153/jfscom.2011009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodine treatment on the hatching rate of black sea turbot, (Psetta maxima Linnaeus, 1758), eggs

Abstract: A study evaluating the effects of iodine treatment on the hatching success of turbot eggs was carried out. A hundred, 500, 1500 and 3000 ppm iodine treatment were performed for 10 minutes. The treatment with 3000 ppm iodine presented lower hatching percentage (70.0 ±6.08%). The control group (97.6 ±1.42%) and disinfected with 100 ppm iodine (91.3 ±4.04%) resulted in slightly higher hatching percentage, and significantly different from the other disinfected groups (P < 0.05). The control group and disinfected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In the second experiment, iodine at concentrations 50, 100 and 250 mg L −1 for 15 showed improvement in the hatching rate and survival to first feeding fry of yellow perch, compared to the control. These results are in accordance with data obtained by Aydın, Polat, Şahin, Kolotoğlu and Ercan (). However, Katharios, Agathaggelou, Paraskevopoulos and Mylonas () observed that 100 mg L −1 iodine for 5 min significantly reduced the hatchability of red porgy Pagrus pagrus and white Sea bream Diplodus sargus sargus eggs compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…In the second experiment, iodine at concentrations 50, 100 and 250 mg L −1 for 15 showed improvement in the hatching rate and survival to first feeding fry of yellow perch, compared to the control. These results are in accordance with data obtained by Aydın, Polat, Şahin, Kolotoğlu and Ercan (). However, Katharios, Agathaggelou, Paraskevopoulos and Mylonas () observed that 100 mg L −1 iodine for 5 min significantly reduced the hatchability of red porgy Pagrus pagrus and white Sea bream Diplodus sargus sargus eggs compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…The latter was done for tilapia ( Oreochromis mossambicus Peters; Subasinghe & Sommerville ), black sea turbot ( Psetta maxima L.; Aydin et al . ), westslope cutthroat trout ( Oncorhynchus clarkii lewisi Suckley; Pravecek & Barnes ) and Atlantic salmon (Jodun & Millard ).…”
Section: Evaluation Criteria For a Successful Disinfectionmentioning
confidence: 99%
“…, ,c; Aydin et al . ), as was the total length of the larvae at hatching (Stuart et al . ), at 19 and 27 days (Dabrowski et al .…”
Section: Evaluation Criteria For a Successful Disinfectionmentioning
confidence: 99%
See 2 more Smart Citations